RELATED PHYSICAL FITNESS IN SCHOOL HEALTH PROGRAM MEMBERS OF ATHLETE OF THE FUTURE OF THE MUNICIPALITY OF ARAPIRACA/AL. (Fiep Bulletin - online, 2014)
The present study aimed to analyze the levels of health-related physical fitness in school Athlete of the members of the city of Arapiraca Future/AL Program. The sample consisted of 44 boys enrolled in the Athlete of the Future Program. The variables studied were: body mass index (BMI), triceps skinfold and subscapular (DCT + DCS); overall strength (measured by running test/caminhada 6 min); force/abdominal strength (average of the abdominal test 1 min), and flexibility (as measured by the sit and reach ). The results were obtained from the normative tables proposed by Lohman and the benchmarks (ZS and ZR) adopted for the assessments ApFRS correspond to those used by Project Sport Brazil. For the treatment of statistical data of central tendency and dispersion values ??(mean and standard deviation) was used. The results regarding the distribution of boys in ZS and ZR, indicate that for cardiorespiratory fitness and abdominal strength/endurance, 54.55% and 93.18 %, respectively, of schoolchildren are below the ZS, while in BMI, 15.90% are situated in the ZR.
Keywords: Physical Fitness; Health; School.